Malaria As An Important Cause Of Maternal Mortality In Sudan - Mohamed EL Sanousi, Mohamed EL Sanousi; AL Hassan, Abdul Rahman Abdul Hafeez; Abd EL Salam, Muawia Mohamed Ahmed (مجلة الجزيرة للعلوم الصحية; مجلد 1 عدد 1 (2004), 2004)
This study was performed to highlight the role of malaria in pregnancy as  an important cause  of maternal mortality. It reviewed the previous studies, conference presentations and postgraduate thesis . Malaria found to be the cause of death of 10.26% to 46.7% of MM. The 1998 to 2003 records of maternal deaths of Wad Medani Obstetrics and gynaecology  teaching hospital (WMOGTH) was retrospectively studies (malaria caused death of 8.82% to 39.7% The mean age was 27.57years , most of them were primigravidae and from rural areas.  37.8% of the deaths occured at 28-36 weak of gestation . The mean duration of stay in hospital was (3.22) days. 32.4% of deaths stayed for less than 24 hours This indicated  severe and serious clinical presentations. The main causes of death due to malaria or its complication  were anemae heart failure  (24.3%), cerebral malaria (21.6%) and  circulatory failure (8.1%). Others were pulmonary edema , hyperpyrexia  , puerperal psychosis , abortion , severe epistaxes , cardiac  arrest , black water fever, electrolyte imbalance, and hepatic failure. The study recommended effective prevention of malaria and an intensive care approach in its management.